Connecting the peninsula and beyond: Italian intellectual networks of the early modern and modern period. An introduction - Meens, Floris (Incontri. Rivista europea di studi italiani, 2019)
Guest editor's introduction to the theme issue Connecting the peninsula and beyond: Italian intellectual networks of the early modern and modern period.